2020
DOI: 10.3390/w13010066
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Autochthonous Bacterial Consortium Obtained from Beach Sediments for Bioremediation of Petroleum Hydrocarbons

Abstract: Oil spill pollution remains a serious concern in marine environments and the development of effective oil bioremediation techniques are vital. This work is aimed at developing an autochthonous hydrocarbon-degrading consortium with bacterial strains with high potential for hydrocarbons degradation, optimizing first the growth conditions for the consortium, and then testing its hydrocarbon-degrading performance in microcosm bioremediation experiments. Bacterial strains, previously isolated from a sediment and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…We found the lowest hydrocarbons degradation in natural attenuation (18%), followed by biostimulation treatment (21%), bioaugmentation with inoculum pre-grown in petroleum treatment (23%), and bioaugmentation with inoculum pre-grown in acetate treatment (30%). The same trend for higher degradation in the BAa (bioaugmentation treatment with inoculum pre-grown in sodium acetate), when compared to BAp (bioaugmentation treatments with inoculum pre-grown petroleum), has been observed in a previous study [37], indicating that this result was associated with the higher bacterial biomass growth obtained in the presence of acetate compared with petroleum.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found the lowest hydrocarbons degradation in natural attenuation (18%), followed by biostimulation treatment (21%), bioaugmentation with inoculum pre-grown in petroleum treatment (23%), and bioaugmentation with inoculum pre-grown in acetate treatment (30%). The same trend for higher degradation in the BAa (bioaugmentation treatment with inoculum pre-grown in sodium acetate), when compared to BAp (bioaugmentation treatments with inoculum pre-grown petroleum), has been observed in a previous study [37], indicating that this result was associated with the higher bacterial biomass growth obtained in the presence of acetate compared with petroleum.…”
Section: Discussionsupporting
confidence: 82%
“…Initially, two different carbon sources, petroleum and sodium acetate, were tested to compare their efficiency to produce high consortium biomass. Being a simple carbon source, sodium acetate is rapidly uptake by most bacteria and had been already tested in previous biodegradation experiments [37]. Our results showed that the HDB_DSS_L1 bacterial consortium grown on sodium acetate was able to survive and grow in petroleum in the bioaugmentation treatment.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Despite the increase of recent studies in bioremediation of petroleum HCs (Chen et al, 2020;Shi et al, 2020;Perdigão et al, 2021), there is still a lack of knowledge regarding the natural repertoire of the microbial communities able to degrade petroleum HCs. This study addresses the geospatial variation of these natural microbial communities in NW coast of the Iberian Peninsula to identify prokaryotic groups with potential bioremediation applicability in this region.…”
mentioning
confidence: 99%
“…In situ and laboratory studies reported that the biodegradation efficiency of petroleum-contaminated sediments can be increased by enhancing biomass and/or activity of hydrocarbon-degrading microorganisms through biostimulation as well as bioaugmentation strategies [ 44 ]. Understanding the factors influencing microbial metabolism and hydrocarbon degradation is crucial to the design of an optimal bioremediation strategy [ 45 , 46 , 47 ].…”
Section: Factors Affecting the Bioremediation Of Sediments Polluted By Petroleum Hydrocarbonsmentioning
confidence: 99%